Manejo geral de suínos criados em sistema intensivo confinado - IFTO – Araguatins-TO - Beleza, Mylianne Thalisa dos Santos (Universidade Federal do Tocantins, 2023)
The objective this report follow the activities developed in the area of swine, Federal institute of Education, Science and Technology of Tocantins (IFTO), campus Araguatins, in the corresponding period of April 24 to June 24, 2014 in order to improve the knowledge acquired during the university. Swine production is an activity that is in full development, highlighting it as the fourth largest producer and exporter of pork, and, well conducted management ensures the success of the production. The activities were related to reproductive management: natural mating, semen collection and artificial insemination; Matrix in gestational stage; Initial management: cut navel, application of iron, mossagem, castration until the establishment of weaning piglets; Nutritional management for each animal type; Sanitary handling: cleaning and disinfecting the premises and Control record, in confined-system intensive breeding.